2016
DOI: 10.1016/j.colsurfb.2016.09.041
|View full text |Cite
|
Sign up to set email alerts
|

Selective anticancer activity of hydroxyapatite/chitosan-poly(d,l)-lactide-co-glycolide particles loaded with an androstane-based cancer inhibitor

Abstract: In an earlier study we demonstrated that hydroxyapatite nanoparticles coated with chitosan-poly(D,L)-lactide-co-glycolide (HAp/Ch-PLGA) target lungs following their intravenous injection into mice. In this study we utilize an emulsification process and freeze drying to load the composite HAp/Ch-PLGA particles with 17β-hydroxy-17α-picolyl-androst-5-en-3β-yl-acetate (A), a chemotherapeutic derivative of androstane and a novel compound with a selective anticancer activity against lung cancer cells. 1H NMR and 13C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 61 publications
1
12
0
3
Order By: Relevance
“…37 Chemotherapeutic derivatives loaded on HAp/Ch-PLGA particles after in vitro studies showed a high potential as fine particle platform for a targeted and selective cancer therapy. 38 Solvent/non-solvent precipitation and freeze-drying were used for the synthesis and processing of HAp coated with Ch or Ch-PLGA nanoparticles with antimicrobial and osteoregenerative properties. 39 A thermogravimetric analysis coupled with on-line mass spectrometry confirmed the coating of the HAp with Ch or Ch-PLGA blend, while in vitro and in vivo studies justified the concept of blending Ch with PLGA in order to increase the quality of osteogenesis.…”
Section: Nano-calcium Phosphate In Bone Tissue Engineeringmentioning
confidence: 99%
“…37 Chemotherapeutic derivatives loaded on HAp/Ch-PLGA particles after in vitro studies showed a high potential as fine particle platform for a targeted and selective cancer therapy. 38 Solvent/non-solvent precipitation and freeze-drying were used for the synthesis and processing of HAp coated with Ch or Ch-PLGA nanoparticles with antimicrobial and osteoregenerative properties. 39 A thermogravimetric analysis coupled with on-line mass spectrometry confirmed the coating of the HAp with Ch or Ch-PLGA blend, while in vitro and in vivo studies justified the concept of blending Ch with PLGA in order to increase the quality of osteogenesis.…”
Section: Nano-calcium Phosphate In Bone Tissue Engineeringmentioning
confidence: 99%
“…Jedna od strategija dizajniranja materijala, na bazi nHAp-a je njihovo ojačavanje sintetskim polimernim matricama poput polil-laktida (PLLA) [56,57], poli(laktid-ko-glikolida), (PLGA) [58] ili prirodnim polimerima poput hitozana [59,60], kolagena [61], celuloze, elastina, keratina itd. [62].…”
Section: Sinteza I Dizajniranje Multifunkci-unclassified
“…Čestice na bazi nHAp/Ch/-PLGA su korišćene kao nosač jedinjenja A, (17β-hydroxy-17α-picolyl-androst-5-en-3β-yl acetate) hemoterapeutskog derivata androstana, koji pokazuje selektivnu antikancerogenu aktivnost prema ćelijama karcinoma pluća [60]. Kompozitni materijal A-HAp/Ch-PLGA bi potencijalno mogao da se koristi za selektivnu terapiju malignih ćelija pluća (slika 7).…”
Section: Sinteza I Dizajniranje Multifunkci-unclassified
See 1 more Smart Citation
“…They exhibit a good biocompatibility compared to other inorganic materials that biodegrade in biological fluids. With such fascinating properties, hydroxyapatite nanoparticles have shown many efforts in the delivery of drug and therapeutic agents with prolonged release [34][35][36][37][38][39]. Hydroxyapatite nanoparticles (HAPs) are of great interest in biomedical applications, such as bone regeneration [40,41].…”
Section: Introductionmentioning
confidence: 99%